Nitrate and fluoride adsorption from aqueous solution by chemically modified palm kernel shells - Bashir, Muhammad Tariq (2016)
Nitrate (NO3-1) and fluoride (F-1) are widespread contaminants in drinking water sources in many countries including Pakistan and detrimental to human health. Palm kernel shell (PKS) is available in abundance in Malaysia as an agricultural waste that can be modified into a water treatment adsorbent by enhancing its affinity to remove anions. This research studied the current NO3-1 and F-1 concentrations in Southern Punjab, Pakistan because there is no monitoring and adequate water treatment system in this region to provide drinking water to the public that is safe and free from pollutants (especially NO3-1 and F-1). Out of 248 samples of drinking water sources in Southern Punjab Pakistan, 11.69% and 8.1% were badly contaminated with NO3-1 and F-1, respectively.An eco-friendly and feasible adsorbent “Chemically Modified Palm Kernel Shell (CMPKS)” was prepared in a two-step process. Firstly, ground PKS particles were exposed to hydroxyl pre-treatment (mercerization) using potassium hydroxide to remove impurities and make the particles porous. Subsequently, the mercerized PKS was quaternized by grafting of N-(3 Chloro-2 Hydroxypropyl) trimethylammonium chloride (CHMAC) under alkaline conditions. Batch studies were conducted to determine the adsorption of nitrate and fluoride on CMPKS at varying contaminant concentrations, adsorbent doses, temperature and pH. Subsequently, the experimental data were simulated using isotherm models, including the Langmuir, Freundlich and Redlich-Peterson models. The adsorption capacity of 54.18 mg/g and 2.35 mg/g was achieved for nitrate and fluoride, respectively. A series of batch tests were also conducted to simulate the adsorption kinetics and thermodynamics of NO3-1 and F-1 removal. Based on the goodness of fit of pseudo-second order model, Elovich Equation and results from the thermodynamic study, the adsorption process was classified as physical adsorption with exothermic and endothermic nature of reactions for nitrate and fluoride, respectively with slight degree of chemisorption. Further, the regenerated CPMKS retained 97% and 98% of its adsorption capacity for nitrate and fluoride, respectively even after five adsorption-regeneration cycles. The sorption capacities and kinetics of the novel CMPKS (adsorbent) in a single and binary system were studied in a continuous flow advanced multi-columns design (AMCD). The sorption capacities were studied in fixed beds and stratified layered columns beds (SLCB). The SLCB shows enhanced efficacy for single and two-component solutions in AMCD. The resulting data were interpreted using the Adams-Bohart and Thomas models, which showed good agreement with the experimental data. Finally, the physicochemical characteristics of CMPKS were determined using scanning electron microscopy, energy dispersive X-ray spectroscopy, Fourier transform infrared spectroscopy, Brunauer-Emmett-Teller analysis, proximate and chemical analyses, and carbon-hydrogen-nitrogen elementary analysis as well as surface charge on CMPKS.In conclusion, the cheap and abundant PKS biomass with two-step chemically modification has excellent potential in removing nitrate and fluoride contaminants in water. In addition, the modified PKS has robust properties and strength which can be reused and regenerated for longer usage in adsorption process to treat contaminated water with nitrate and fluoride pollution. Subsequently, this shall reduce the operating and capital cost of the treatment process and very suitable for poor countries.